THE DIFFICULTY FOUND IN COMPANIES FOR THE IMPLEMENTATION OF AN ERP SYSTEM – ENTERPRISE RESOURCE PLANNING - Lopes, David Anderson; Freire, José Eduardo (Revista Interface Tecnológica, 2022)
Staying in such a competitive job market and with the speed of information is not an easy task. And for this it is always necessary for companies to update themselves, and a way to update themselves, have quick information and be a competitive differential is the use of an ERP - Enterprise Resource Planning that has enables the integration between all departments of the company generating reports and important information within the company. The objective of this work was to verify through a bibliographic survey the difficulties encountered by companies for the implementation of an ERP - Enterprise Resource Planning and to present Case Studies that demonstrate the difficulties encountered for the implementation of an ERP in a company. The methodology used in this research was the bibliographic research and the case study. The results achieved with this research was the identification of the main problems for the implantation of an ERP that the human factors is the main difficulty for the implantation of an ERP in a company.
Keywords: ERP; ERP Implementation Difficulty; ERP Implementation Case Study